(Homo)sexualidade em diálogo: imaginário cristão, intolerância religiosa e cisma anglicano - Carvalho, Elton Roney da Silva (2014)
The theme of this work is understood in the field of Science of Religions , specifically in the area of Cultures and Religions Symbolic Productions , and was investigated according to the method of Critical Discourse Analysis , with the methodology to bibliographic and documentary research . Searching verify the following hypothesis : the call (post ) modernity attracted to the Christian community , the new biblical interpretation about homosexual practice , creating not only the acceptance of the practice , as well as the growth of inclusive churches and the emergence of movements of religious intolerance ; as seen in the schism occurred in the Anglican Episcopal Church of Brazil . Aims to analyze the current dialogue between the ( homo ) sexuality and Christianity . Uploaded objectively debate in the Christian imagery of homosexual practice , religious intolerance that can be seen in our world (post ) modern, in the ecclesiastical schism occurred in the Anglican Episcopal Church of Brazil . The study is structured in four chapters . In the first chapter , we intend to analyze the influence that the imaginary Christian Catholic Apostolic Roman aroused the Brazilian people to form the understanding of homosexual practice , since, in the specific case of Brazil , the presence of the Roman Catholic Church contributed to the formation of the local culture of this country . Then, we intend to analyze the current relationship between Christianity and homosexuality in Brazil . This analysis pervades the biblical interpretations and major points of contemporary Christian moral arguments about this practice . The third chapter aims to discuss the new dialogues generated by postmodernity and the impact it has had on Christianity, specifically with regard to the doctrines of fundamentalism and the emergence of queer theology. The fourth chapter focuses on analyzing the current debate about the relationship between the acceptance of homosexuality by faithful Anglicans and the ecclesiastical schism occurred in the Anglican Diocese of Recife ; generating the excommunication of Bishop Robinson Cavalcanti . Also discussed the historical formation of the Anglican Church in Brazil , with interest to understand the formation of the Anglican doctrine and posture about sexuality in Brazil